Efektifitas Membaca Nyaring Untuk Meningkatkan Kemampuan Membaca Siswa pada Sekolah Menengah - arjunina maqbulin (Inovasi-Jurnal Diklat Keagamaan, 2022)
In teaching reading, especially for senior high school students, they have to master high reading skills such as inferential, evaluative and critical reading. To reach this purpose, many teachers ask the students to read silently through skimming or scanning. However, some researches have proven that using reading aloud in teaching reading can improve students vocabulary and make students idea sharpener in finding detail information of the text. in addition, reading aloud is related a lot with reading comprehension. That is why it is important to know whether or not reading aloud is needed for teaching reading for senior high school. The aim of this research is to answer a research question, it is about whether or not reading aloud can improve students’ reading ability. The method used in this research is quantitative. The data used in this research is the result of pre-test and post-test of experimental and control class which are taken from the twelve grade students of MAN 2 Nganjuk, Academic year 2022/2023. The result of this research shows that reading aloud can improve the students’ reading ability, or on the other word, there is a significance different of the students’ score after being taught by using reading aloud strategy. The next research about this strategy for higher students of EFL with different type of text is needed so it can be used as the references for teachers to improve their strategy for teaching reading.